NUTRIENT TRANSFER IN VESICULAR-ARBUSCULAR MYCORRHIZAS: A NEW MODEL BASED ON THE DISTRIBUTION OF ATPases ON FUNGAL AND PLANT MEMBRANES - F.A. SMITH; S.E. SMITH (SEAMEO BIOTROP, 1995)
In this paper we review the membrane transport processes that are involved in the transfer of mineral nutrients and organic carbon between the symbiotic partners in mycorrhizas. In particular, we reassess the prevailing hypothesis that transfer in vesicular-arbuscular (VA) mycorrhizas occurs simultaneously and bidirectionally across the same interface and that arbuscules are the main sites of transfer. Using cytochemical techniques, we and our collaborators have reexamined the distribution of ATPases in the arbuscular and intercellular hyphal interfaces in VA mycorrhizas formed between roots of Allium cepa (onion) and the fungus Glomus intraradices. The results showed that H+-ATPases have different localisation on plant and fungal membranes in arbuscular and hyphal interfaces (Gianinazzi-Pearson et al. 1991). While some arbuscular interfaces had H+-ATPase activity on both fungal and plant membranes, in most cases the fungal membrane lacked this activity. In contrast, the plasma membranes of intercellular hyphae always had H+-ATPase and the adjacent root cells did not. This suggests that the different interfaces in a VA mycorrhiza may have different functions. We propose that passive loss of P from the arbuscules is associated with active uptake by the energised (ATPase-bearing) plant membrane and that passive loss of carbohydrate from the root cells is followed by active uptake by the intercellular hyphae. If this model is correct, then variations in